2018
DOI: 10.1093/mnras/sty2653
|View full text |Cite
|
Sign up to set email alerts
|

The Ophiuchus DIsc Survey Employing ALMA (ODISEA) – I: project description and continuum images at 28 au resolution

Abstract: We introduce the Ophiuchus DIsc Survey Employing ALMA (ODISEA), a project aiming to study the entire population of Spitzer -selected protoplanetary discs in the Ophiuchus Molecular Cloud (∼300 objects) from both millimeter continuum and CO isotopologues data. Here we present 1.3 mm/230 GHz continuum images of 147 targets at 0.2 (28 au) resolution and a typical rms of 0.15 mJy. We detect a total of 133 discs, including the individual components of 11 binary systems and 1 triple system. Fifty-three of these disc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

21
204
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 209 publications
(226 citation statements)
references
References 90 publications
(94 reference statements)
21
204
0
1
Order By: Relevance
“…7. Most of the disks in our sample have masses below the minimum mass solar nebula and sizes < 30 au, in agreement with the Class II disks reported by Cieza et al (2019). We find that our sample of disks follow a surface density relation of Σ ∼ r −(0.9−0.6) .…”
supporting
confidence: 89%
See 1 more Smart Citation
“…7. Most of the disks in our sample have masses below the minimum mass solar nebula and sizes < 30 au, in agreement with the Class II disks reported by Cieza et al (2019). We find that our sample of disks follow a surface density relation of Σ ∼ r −(0.9−0.6) .…”
supporting
confidence: 89%
“…Figure 2 shows that the field also contains 4 additional compact objects, including a more evolved YSO, IRS 39, 15 southwest of the phase center. Several of the aforementioned compact objects were also detected by Cieza et al (2019) in their ALMA 1.3 mm emission. We use a similar naming scheme as Cieza et al (2019), Figure A8.…”
mentioning
confidence: 96%
“…These observed disks surrounding a range of host-stellar masses have gas radii in the range of 63-500 AU at an age of ∼ 1-3 Myr. We emphasize, however, that these large, extended disks are the exception and are not indicative of typical disks that are much more compact, as indicated by numerous observations showing dust radii of 20 − 30 AU (Barenfeld et al 2016(Barenfeld et al , 2017Cox et al 2017;Hendler et al 2017;Tazzari et al 2017;Cieza et al 2019;Long et al 2019).…”
Section: Introductionmentioning
confidence: 67%
“…(ii) Planet formation simulations are missing some important ingredients regarding gas accretion (see also Nayakshin et al (2019)) and planet migration. The survey by Long et al (2018) in the Taurus star-forming region and the survey by Cieza et al (2019) in the Ophiuchus starforming region, on the other hand, found a significant population of very compact discs (outer disc radii ¡ 30 au). These discs are not pictured within the DSHARP sample, due to the selection biases in the DSHARP campaign (Andrews et al 2018).…”
Section: Discussionmentioning
confidence: 95%